PENINGKATAN LITERASI KEUANGAN SYARIAH MELALUI PENGEMBANGAN MODUL PEMBELAJARAN DI SD INPRES 5/81 WATU - Astiana; Hamzah, Aksi; Buhasyim, Abdi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the improvement of Islamic financial literacy through the development of learning modules at SD Inpres 5/81 Watu, Bone Regency. The module is designed to provide early financial education tailored to elementary school children's comprehension level. Using qualitative descriptive methods, data collection was carried out through observation, interviews, and documentation. The results indicate that the module significantly improved students' understanding, awareness, and behavior related to Islamic finance. The study recommends interactive and practical educational strategies to address the challenges of financial literacy in schools.